Mining of Data with Complex Structures - Hadzic, Fedja; Tan, H.; Dillon, Tharam (Springer, 2011)
Table of Contents: Introduction - Tree Mining Problem - Algorithm Development Issues - Tree Model Guided Framework - TMG Framework for Mining Ordered Subtrees - TMG Framework for Mining Unordered Subtrees - Mining Distance-Constrained Embedded Subtrees - Mining Maximal And Closed Frequent Subtrees - Tree Mining Applications - Extension of TMG Framework for Mining Frequent Subsequences - Graph Mining - New Research Directions.